Developing Internet research skills among criminology honours students and researchers in the Institute of Criminology, University of Cape Town : an evaluation of the methods and materials used for this purpose - Atkins, Elaine (Library and Information Studies Centre (LISC), 2014)
Bibliography: leaves 62-66.